Roles of hypoxia inducible factors in viral infection: Are they a potential therapeutic target? - Sikai Jia; Shuo Pan; Zhiyun Gao; Hongxiu Qiao; Yan Zhao; Xia Chuai; Jian Li (Virulence)
As a crucial nuclear transcription factor, hypoxia-inducible factor (HIF) serves essential functions in mediating cellular responses to hypoxic stress. Through oxygen-sensing mechanisms, HIF initiates downstream signaling cascades that coordinate metabolic reprogramming, immune modulation, and oncogenic progression in oxygen-deficient microenvironments. Current evidence positions HIF at the convergence of various pathologies, including microbial pathogenesis, carcinogenesis, and inflammatory disorders. This systematic review summarizes recent advances in HIF-mediated immunomodulation and virological mechanisms. The analysis emphasizes the fundamental importance of investigating HIF-related molecular pathways to address significant gaps in basic research.